(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Pineapple guarapo, considered the drink of the Colombian people, is a fermented drink that has unique characteristics thanks to the fermentation process. However, due to the arrival of large brewing industries, this drink has been disappearing, representing damage to the country’s cultural heritage and identity. The present work proposes to establish the physicochemical and microbiological parameters for the pineapple guarapo production process using two fermentation processes: controlled (Saccharomyces cerevisiae var. Diastaticus) and uncontrolled. The physicochemical characterization of the pineapple and panela used in the guarapo production process was determined through the measurement of ° Brix, pH, humidity, ash, acidity and density. The production process of the two types of pineapple guarapo was developed under the same time and temperature conditions. Finally, the characteristics of the fermented drinks were determined through physicochemical, microbiological and sensory tests. The results show that the percentage of ashes and alcohol differ the most between the two drinks obtained. Microbiological analyzes demonstrated a high microbial load, being 216,300,000 cells/mL in the guarapo obtained by controlled fermentation. Furthermore, the sensory evaluation shows that the drink with uncontrolled fermentation was more accepted mainly due to its taste and smell, while the other drink stands out for its high alcohol content. Finally, it was possible to establish the physicochemical and microbiological parameters for the pineapple guarapo production process using the two mentioned fermentation processes.